2016
DOI: 10.1111/opo.12342
|View full text |Cite
|
Sign up to set email alerts
|

The heterophoria of 3–5 year old children as a function of viewing distance and target type

Abstract: Purpose Heterophoria is the misalignment of the eyes in monocular viewing and represents the accuracy of vergence driven by all classical cues except disparity. It is challenging to assess restless children using clinical cover tests, and phoria in early childhood is poorly understood. Here we used eye tracking to assess phoria as a function of viewing distance and target in adults and young children, with comparison to clinical cover tests. Methods Purkinje image tracking (MCS PowerRefractor) was used to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
4
6
0
Order By: Relevance
“…One, we did not find difference in the drifts, if the vergence angle was responsible then we would find differences in both drifts and saccades. Two, previous studies have reported similar amounts of vergence at the viewing distance used in the current study[ 63 – 65 ].…”
Section: Discussionsupporting
confidence: 69%
“…One, we did not find difference in the drifts, if the vergence angle was responsible then we would find differences in both drifts and saccades. Two, previous studies have reported similar amounts of vergence at the viewing distance used in the current study[ 63 – 65 ].…”
Section: Discussionsupporting
confidence: 69%
“…The 95% limits of agreement obtained in the current study were comparable with the ones obtained by Babinsky et al on a sample of young children [ 16 ]. Recently, Troyer et al obtained slightly better agreement than Babinsky yet still comparable values between cover test and objective measurements in both children and adults [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“… 40 Similarly, standard heterophoria testing and power refractor objective testing of heterophoria with movies vs. a standard clinical target did not result in significant differences. 24 As such, we can assume that the use of a penlight for our cover testing and ET protocol yield similar results to accommodative targets, but future investigations should include a systematic comparison of target type and its effect on subjective and objective heterophoria testing.…”
Section: Discussionmentioning
confidence: 92%
“…Babinsky et al 2 reported the normative values of heterophoria using an IR-filter as a cover over the right eye and a 25-Hz PowerRefractor recording of the eye position. The PowerRefractor has also been used by others to objectively assess heterophoria in children 24 and adults. 3 Recently, an automated system of eye tracking at 60 Hz with a synchronous controlled sliding occluder for cover testing has been reported.…”
Section: Introductionmentioning
confidence: 99%